Artificial Intelligence Application in Power Generation Industry: Initial considerations - Ismail R.I.B.; Ismail Alnaimi F.B.; Al-Qrimli H.F. (Institute of Physics Publishing, 2023)
Artificial intelligence; Competition; Condition monitoring; Genetic algorithms; Iterative methods; Neural networks; Problem solving; Fault detection and diagnosis; Faults detection; Intelligent condition monitoring; Mitigation measures; Nonlinear iterations; Plant operations; Power generation industries; Problem-solving abilities; Fault detection; artificial intelligence; artificial neural network; competitiveness; genetic algorithm; industrial technology; monitoring system; power generation; power plant